Serological Diagnosis of Paracoccidioidomycosis through a Western Blot Technique - Perenha-Viana, M. C. Z. (American Society for Microbiology, 2012)
Paracoccidioidomycosis (PCM) is a serious infectious disease that progresses toward death if untreated. Its confirmatory diagnosis is made by the detection of the fungus Paracoccidioides brasiliensis in a direct mycological examination or by histopathology. However, these techniques are of low sensitivity. Serological tests seem to be more promising. The objective of this study was to test Western blot (WB) analysis using sera from patients suspected of PCM to determine whether it represents a safe and sensitive serological technique for a rapid and effective diagnosis for this disease. Sera from 517 patients were analyzed through WB analysis and double-immunodiffusion (DID) techniques using a crude exoantigen of P. brasiliensis 339. DID gave positive reactions for 140 sera (27%) and WB for 250 sera (48.4%). All sera that had a positive reaction by DID also had a positive result with a 43-kDa glycoprotein by WB analysis. Among the 377 samples that were negative by DID, 29.1% were reactive in WB analysis. For the cutoff dilution used (1:400), a positive reaction was not observed with any of the 102 sera from patients with other diseases in regions where such diseases are endemic and 30 healthy individuals tested as negative controls. These results prove WB analysis to be a sensitive technique and suggest its inclusion among routine laboratory assays as a safe method for PCM diagnosis.